STRATEGI IMPLEMENTASI CONTINOUS IMPROVEMENT DI PKPBA UIN MAULANA MALIK IBRAHIM MALANG : STUDI KASUS: Strategi Implementasi Continous Improvement di PKPBA UIN Maulana Malik Ibrahim Malang: Studi Kasus - Mulyani, Rinda Eka; Adjiji, Fatma Dewi (Transformation of Islamic Management and Education, 2025)
Improving the quality of Arabic language instruction in Islamic higher education requires a management system oriented towards continuous improvement. This study aims to analyse the implementation strategy of continuous improvement in the management of the Special Programme for Arabic Language Courses (PKPBA) at UIN Maulana Malik Ibrahim Malang. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with institutional leaders, programme coordinators, lecturers, and academic support staff, as well as observations of learning activities and programme management practices. Supporting data were obtained from institutional documents and relevant literature. Data credibility was ensured through source and method triangulation as well as member checking. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that PKPBA has systematically implemented a continuous improvement strategy through the Plan–Do–Check–Act (PDCA) cycle. This strategy is reflected in needs-based planning through placement tests, differentiated learning organisation, tiered instructional implementation supported by information technology, and comprehensive evaluation aimed at ongoing quality enhancement. The results indicate that the application of continuous improvement contributes positively to the effectiveness of programme management and the sustainability of Arabic language learning quality. This study concludes that the continuous improvement model implemented by PKPBA can serve as a reference for the development of Arabic language learning management in Islamic higher education institutions.